2021
DOI: 10.1016/j.ajo.2020.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Sector Retinitis Pigmentosa: Extending the Molecular Genetics Basis and Elucidating the Natural History

Abstract: Purpose To determine the genetic background of sector retinitis pigmentosa (RP) natural history to better inform patient counseling. Design Retrospective case series. Methods Review of clinical notes, retinal imaging including color fundus photography (CFP), fundus autofluorescence (FAF), optical coherence tomography (OCT), electrophysiological assessment (ERG), and molecular genetic testing were performed in patients with sector RP from a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Rhodopsin ( RHO , OMIM 180380) can cause a range of (RCD) phenotypes, including typical RCD, sector RP, pericentral RP and CSNB 116 . The severity of RHO ‐associated phenotypes varies significantly, from asymptomatic to severe disease.…”
Section: Rod‐cone Dystrophiesmentioning
confidence: 99%
“…Rhodopsin ( RHO , OMIM 180380) can cause a range of (RCD) phenotypes, including typical RCD, sector RP, pericentral RP and CSNB 116 . The severity of RHO ‐associated phenotypes varies significantly, from asymptomatic to severe disease.…”
Section: Rod‐cone Dystrophiesmentioning
confidence: 99%
“…Sector RP is an uncharacteristic form of RP where only one or two quadrants of the retina are affected, in most cases inferior or nasal parts of the retina (superior visual field defects) possibly due to greater UV light exposure [ 25 , 39 ]. Sector RP has a favorable visual prognosis compared to generalized RP; it has been reported that 82% of cases will retain a visual acuity (VA) of 20/40 or better [ 39 ]. Generally, it is therefore considered a stationary to slowly progressive disease but may eventually lead to a more severe, diffuse RP phenotype [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study includes three cases with long-term re-assessment, including one patient evaluated after more than 30 years of disease, which clearly demonstrates the evolution in her clinical and electrophysiologic findings. A recent study of the etiology of sector RP across a variety of genotypes was conducted by Georgiou et al [ 19 ], including RHO variants, and suggested that any progression that was noted up to 6 years of follow-up was small in extent with little clinical impact. While we agree with the authors’ conclusion that the long-term prognosis for central visual acuity is good in many of these patients, significant progression in the disease with clinical and functional impact on peripheral vision can occur over longer periods in RHO p.Gly106Arg disease.…”
Section: Discussionmentioning
confidence: 99%
“…The RHO c.316G > A, p.Gly106Arg variant was first described as a cause of autosomal dominant sector RP in four patients with a distinct phenotype characterized by pigmentary changes in the inferior retina and corresponding visual field impairment in the superior hemisphere [18], with a good central visual prognosis. This inferior sectoral phenotype was subsequently seen in five other patients [19,21,22], including three from the same family [21]. A careful review of the reported cases, however, shows that at least one of these patients had more extensive near-peripheral anatomic involvement and evidence of a pericentral ring scotoma on visual fields [21].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation